5 - L’agriculture périphérique dans le nouvel ordre international: Réflexions sur la question des systèmes alimentaires nationaux - VERGOPOULOS, Kostas (Africa Development, 1981)
The author argues that the present economic crisis , reflected the underdeveloped countries by unfavourable terms of exchange for materials and increases in oil prices , calls for radical changes in the role agriculture. For the semi-industrialized countries , continued international competitiveness and foreign exchange constraints call for increased domestic food production while for the least developed countries mere survival also demands increased self-sufficiency in food production. Thus, for reason or another, food self-sufficiency has become agoalforall periphery countries. This Imperative for food self-sufficiency is imposed by the urban economic system in the Third World which is transforming, in varying degrees, the formerly parasitic urban centers into industrial centers. These transformations of urban space imply mutations in the relations between agriculture and industrial sectors in response to modifications of the local demand structure for urban products. While the traditional international demand was essentially for agricultural and mineral raw materials, the new urban demand is directed towards food crops. Secondly, while international demand encouraged monocultural specialization, the new urban demand calls for diversification of production and the devolpment of polycultural production. Thirdly , while past urban consumption tended to be predominantly oligarchic and parasitic, the new demand is mass oriented being generated by the increase urban labour force. And finally, while in the past the cost of agricultural production was limited to wages of farm workers , rents and profits remaining intact , under the new system , all social costs are taken into account and competitiveness on the world market calls for the reduction of all costs. This concomitant mutation in the structure of demand has meant that agriculture is not viewed as merely the production of raw materials but as parts of a process leading to the final industrial transformation of agricultural products for the local urban market. This need for local industrial transformation of agricultural products accounts for increasing presence of transnational agrobusiness in periphery economies. As a result of the implantation of transnational firms in food-processing , there is a risk that these firms may move directly into the agricultural sector itself given these firms strategies of vertical integration. This process of vertical integration , leading to high profits for transnational corporations, will have adverse effects on the costs of reproduction of labour in the urban areas thus reducing the competitiveness of periphery economies in the world economy. Two options are open for food policies of Third World economies : (a) nationalization of the agroindustrial sector in order to suppress the excessive profits accruing to agrobusiness. This will lower the cost of wage goods and enhance international competitiveness. (b) The state may support control by peasants associations and cooperatives from the farm, through food processing up to retail to consumers thus reducing the role of private agroindustrial firms. The first option, while reducing superprofits and lowering wage goods, may, by reducing peasants to a salariat and by its inherent bureaucratic features, damp the peasant initiative and lead to decline in production. The second alternative, by converting peasants into responsible producers, while containing advantages of the first option, does not have any of the disadvantages. It stimulates the productive initiative of the peasants while permitting state control through its financial means. The author concludes that while this organizational autonomy is only wthin a global capitalist system, it can also assume a different form by being a part of different global system of generalized self-management (autogestion). Kostas VERGOPOULOS, Professeur au Département d'Economie politique de l'Université de Paris VIII. Je tiens à remercier ici les amis, professeurs, chercheurs et étudiants, de l'Université centrale de Vénézuela, en particulier les ani- mateurs du Curso de Postgrado de la Faculté d'Agronomie, du Centro de Estudios del Desarrolo, ainsi que du CIARA, pour leur contribution précieuse dans l'élaboration des thèmes traités. Le CODESRIA adresse ses sincères remerciements à la Revue Tïers- Monde pour lui avoir permis de publier cet article